Relasi Aktor Governance dalam Penanganan Covid-19 di Indonesia - Ummu Habibah Gaffar; Sri Mujiarti Ulfah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2021)
The second wave of Covid-19 has hit Indonesia in the last few months. This marks a new chapter for the Covid-19 variant in Indonesia, which is indicated by a very high transmission rate. At the same time, the government is trying to take preventive measures to prevent the spread of Covid-19, one of which is a call for a Covid-19 vaccine. In this regard, this article will look at the relationship between governance actors in efforts to prevent Covid-19 in Indonesia, with an emphasis on the involvement of civil society and private actors in handling Covid-19 in Indonesia. By using a qualitative method, this article takes a literature study by comparing the results of observations made by observing the development of Covid-19 and the involvement of various actors, especially in terms of preventing Covid-19 such as vaccination. This article concludes that the spread of Covid-19 is still very high, meanwhile the involvement of actors in handling Covid-19 tends to be limited and closed. The actors involved are mostly dominated by the government, while the private sector and civil society have not been involved much. This article will contribute at least practically, to be discussed further, especially to formulate a scheme for the involvement of other actors outside the government, while still prioritizing the security and welfare of the community.